Madrasah Principal Leadership Strategies for Graduate Quality Development - Muhammad In’am Esha; Muhammad Rizky Mubarok; Nurul Yaqien (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Globalization and technological advancement require educational institutions to produce graduates with academic excellence, strong character, and relevant competencies. Specific Background In Islamic education, madrasah principals hold a strategic position in managing institutional programs that support graduate quality through planning, implementation, and evaluation. Knowledge Gap Educational institutions still face challenges related to learning quality, limited facilities, and human resource management, making principal leadership strategies important to examine in relation to graduate quality development. Aims This study analyzes madrasah principal leadership strategies in developing graduate quality through three main aspects: strategy planning, strategy implementation, and strategy evaluation. Results The findings show that planning was conducted systematically and based on institutional needs, focusing on human resource quality, outcome-based intensive programs, technology-based facilities and infrastructure, student career guidance, and character strengthening through extracurricular activities. Implementation was carried out through interconnected input, process, output, and outcome approaches. Evaluation was conducted continuously through academic supervision, program audits, and participatory evaluation involving various stakeholders. The strategy supported graduate quality in academic achievement, character formation, and competitiveness for continuing education, with 84% of students accepted into state universities. Novelty This study presents an integrated leadership strategy model that connects needs-based planning, systematic implementation, and continuous evaluation in madrasah graduate quality development. Implications Madrasah leadership should prioritize sustainable program evaluation, resource development, learning innovation, and career guidance to prepare graduates for future academic and social challenges. Highlights: Planning focused on human resources, facilities, careers, and character. Program execution followed input, process, output, and outcome stages. Continuous supervision and audits supported student competitiveness. Keywords: Leadership, Head of Madrasah, Education, Graduate Quality, Islamic Education Management